Vertical and depth jumping performance in elite athletes from different sports specialties - Kobal, R.; Nakamura, F. Y.; Kitamura, K.; Cal Abad, C. C.; Pereira, L. A.; Loturco, I. (Science & Sports, 2017)
Objectives: This study aimed to compare the differences in vertical jumping abilities between top-level athletes from distinct sports specialties.